1979
DOI: 10.1002/path.1711280402
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural and immunohistochemical study on the δ antigen associated with the hepatitis B virus

Abstract: Thirteen liver biopsies in which the delta antigen was detected by immunofluorescence were studied by electron microscopy and immune electron microscopy with peroxidase labelled IgG and F(ab1)2 fraction obtained from a human antiserum containing high-titre anti-delta antibodies. The findings were compared with those obtained in 11 HBcAg positive and in two HBsAg negative controls. Neither unique particulate morphology nor any HB virus ultrastructural component were visualised in the delta positive specimens; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…The standard anti-3-Ag antiserum was obtained from a patient with chronic persistent type B hepatitis and contained a high titer of anti-3-Ag [1:1000 by immunofluorescence (1); 1:105 by a blocking radioimmunoassay (3)], a low titer of antiHBc (1:600 by radioimmunoassay), and no HBeAg, anti-HBs, or anti-HBe activity by radioimmunoassay. The optimal dilution of the standard anti-3-Ag serum (1:1000) was previously established by checkerboard titration against a preparation of b-Ag extracted from a b-Ag-positive human liver (2). Serum samples were tested before and after treatment with different concentrations of Nonidet P-40.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard anti-3-Ag antiserum was obtained from a patient with chronic persistent type B hepatitis and contained a high titer of anti-3-Ag [1:1000 by immunofluorescence (1); 1:105 by a blocking radioimmunoassay (3)], a low titer of antiHBc (1:600 by radioimmunoassay), and no HBeAg, anti-HBs, or anti-HBe activity by radioimmunoassay. The optimal dilution of the standard anti-3-Ag serum (1:1000) was previously established by checkerboard titration against a preparation of b-Ag extracted from a b-Ag-positive human liver (2). Serum samples were tested before and after treatment with different concentrations of Nonidet P-40.…”
Section: Methodsmentioning
confidence: 99%
“…After extraction from hepatocyte nuclei with guanidine hydrochloride, b-Ag was characterized as a protein with a molecular weight of approximately 68,000 (2). Although b-Ag has not been detected in the sera of patients with intrahepatic b-Ag, such individuals develop high titers of anti-3-Ag which might interfere with the available solid-phase radioimmunoassay for b-Ag.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The tubular and reticular abnormalities were coincident with the reexpression of HDAg in liver biopsies and abnormal ALT levels. Canese et al (26) reported identical ultrastructural abnormalities in chimpanzees infected with the same inocula.…”
Section: Modelsmentioning
confidence: 86%
“…Subsequently, human sera containing high titers of anti-HD and low titers of anti-HBc activity were labeled with horseradish peroxidase and used for the direct detection of HDAg by immunoperoxidase staining of frozen sections and paraffin-embedded sections from patients with chronic liver disease (26,82,194 (95,179). In the assay described by Shattock and Morgan (179), Tween 20 is used to release the antigen from the HBsAg envelope.…”
Section: Methods Of Detecting Hdvmentioning
confidence: 99%